Ambiguity in English Test Bias on Buku Jagoan: Langsung Lulus UASBN SD / MI 2013 - Murniati Murniati (Universitas Bunda Mulia, 2020)
This research aims to find the ambiguity found in the English test of the school final exam (Ujian Akhir Sekolah Dasar). The ambiguity which is considered as a test bias, may affect both validity and reliability of the test which in the end will affect the grade gained by the test takers. The data is gained from the test items printed in the book which is sold in the bookstore. Each item will be analyzed whether it has one correct answer or not. After the test ambiguity is found, alternative test items will be proposed in order that the test will be free of the test bias so that the test can be considered as valid and reliable.